2012
DOI: 10.1103/physrevb.85.205137
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of hydration and oxidation in the proton conductor Gd-doped barium cerate from density functional theory calculations

Abstract: Hydration and oxidation of gadolinium-doped barium cerate, a system with highly promising properties when used as electrolyte for protonic ceramic fuel cells, are investigated by means of density functional calculations. The energy landscape of oxygen vacancies and interstitial protons in this strongly distorted orthorhombic perovskite is computed. Although the most stable sites for protons are found in the close vicinity of the dopant, the picture of a very complex energy landscape emerges, in which some site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 66 publications
5
70
1
Order By: Relevance
“…Hermet et al 35 . The relative stability between the isolated point defects and their associated forms; ሺX େୣ OH ) × and ሺX େୣ v ) • , is given by their respective association enthalpies.…”
Section: Defect Energetics From Dft Calculationsmentioning
confidence: 99%
“…Hermet et al 35 . The relative stability between the isolated point defects and their associated forms; ሺX େୣ OH ) × and ሺX େୣ v ) • , is given by their respective association enthalpies.…”
Section: Defect Energetics From Dft Calculationsmentioning
confidence: 99%
“…Theoretically, previous studies have revealed that advanced electronic structure calculations are needed to correctly describe this oxidation phenomenon. Indeed, the generalized gradient approximation (GGA) finds it exothermic in several perovskite oxides [10][11][12], while hybrid functionals (PBE0) provide an endothermic picture [12]. This is related to the band-gap problem, more precisely to the incorrect position of the valence band maximum, formed by oxygen-2p states, obtained with GGA.…”
Section: ••mentioning
confidence: 99%
“…[39,40]. It may, however, be more accurate to consider the structural relaxation around dopant-vacancy pairs, or even extended Y-V O -Y defects, remembering that two dopants ions are required per oxygen vacancy and that a strong associative attraction between the positively charged vacancies and the acceptor dopants is expected from computational studies, see for example refs.…”
Section: I) Role Of Yttrium Dopant and Oxygen Vacancies On The Crystamentioning
confidence: 99%